Strength and conditioning a biomechanical approach - Moir, Gavin (Jones & Bartlett Learning, 2016)
Written for both the undergraduate/graduate level student as well as practitioners in the field, this text incorporates all programming aspects of strength and conditioning including training methods to develop muscular strength and power, flexibility, and the development of effective warm-up regimens. Performance analysis techniques in sport are introduced while the constraints-led approach to motor skills acquisition is presented as a framework that can guide the development of practices for the strength and conditioning practitioner. The biomechanical and motor skill acquisition concepts introduced in the text are then applied to fundamental movements including jumping, landing, and sprint running. Key Features: - Provides a solid introduction to biomechanics pertinent to the study of human movements - Discusses the performance analysis techniques in sport that can be used by the strength and conditioning practitioner to determine the physiological, mechanical, and technical demands of specific sports, and also the assessment of the techniques used in the execution of sport-specific skills - Includes a critical review of the different approaches to motor skill acquisition - Incorporates clear learning objectives and worked examples in each chapter that allow readers to apply the concepts to real-life situations - Discusses the application of the most recent research pertinent to concepts in each chapter - Includes appendices to expand on some of the more complex mathematical techniques required to perform biomechanical analyses and useful resources to aid the student in locating and evaluating scientific evidence.